Impact of Healthcare-Associated Infections on Length of Stay: A Study in 68 Hospitals in China. (18th April 2019) - Jia, Huixue; Li, Liuyi; Li, Weiguang; Hou, Tieying; Ma, Hongqiu; Yang, Yun; Wu, Anhua; Liu, Yunxi; Wen, Jianguo; Yang, Huai; Luo, Xiaoli; Xing, Yawei; et al.
Abstract : Healthcare-associated infections (HAIs) not only bring additional medical cost to the patients but also prolong the length of stay (LOS). 2119 HAI case-patients and 2119 matched control-patients were identified in 68 hospitals in 14 primary sampling provinces of 7 major regions of China. The HAI caused an increase in stay of 10.4 days. The LOS due to HAI increased from 9.7 to 10.9 days in different levels of hospitals. There was no statistically significant difference in the increased LOS between different hospital levels. The increased LOS due to HAI in different regions was 8.2 to 12.6 days. Comparing between regions, we found that the increased LOS due to HAI in South China is longer than other regions except the Northeast. The gastrointestinal infection (GI) caused the shortest extra LOS of 6.7 days while the BSI caused the longest extra LOS of 12.8 days. The increased LOS for GI was significantly shorter than that of other sites. Among 2119 case-patients, the non-multidrug-resistant pathogens were detected in 365 cases. The average increased LOS due to these bacterial infections was 12.2 days. E. coli infection caused significantly shorter LOS. The studied MDROs, namely, MRSA, VRE, ESBLs- E. coli, ESBLs-KP, CR- E. coli, CR-KP, CR-AB, and CR-PA were detected in 381 cases (18.0%). The average increased LOS due to these MDRO infections was 14 days. Comparing between different MDRO infections, we found that the increased LOS due to HAI caused by CR-PA (26.5 days) is longer than other MDRO infections (shorter than 19.8 days).